105k views
0 votes
Find the 7th term in the
sequence
-1, -3, -9,...

User Judoman
by
5.6k points

2 Answers

4 votes

Answer:

The answer is 729

Step-by-step explanation:

to get the next term, the sequence multiples the previous number by -3

1 * -3 = -3

-3 * -3 = 9

and so on.

To get the 7th term:

-27 * -3 = 81 (5th term)

81 * -3 = -243 (6th)

-243 * -3 = 729 (7th)

User Pasztorpisti
by
6.4k points
4 votes

Answer:

The seventh term in the sequence is -729.

Explanation:

Notice that the sequence is not increasing linearly. Therefore, this is a geometric sequence.

Recall that the explicit formula for a geometric sequence is given by:


x_n=a(r)^(n-1)

Where a is the first term, r is the common ratio, and n denotes the nth term.

From the sequence, we can see that our first term a is -1.

Because each term is thrice the previous, our common ratio r is 3.

By substitution:


x_n=-(3)^(n-1)

Hence, the seventh term is:


\displaystyle \begin{aligned} x_7 & = -(3)^((7)-1) \\ \\ & = -(3)^(6) \\ \\ & = -729\end{aligned}

In conclusion, the seventh term is -729.

User Nicholas Cardot
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.